Mutual Information and Cross Entropy Framework to Determine Relevant Gene Subset for Cancer Classification - Bala, R.; Agrawal, R.K. (Informatica)
Mutual Information and Cross Entropy Framework to Determine Relevant Gene Subset for Cancer Classification